ANALISIS PERTUMBUHAN TANAMAN DAN KOMPONEN HASIL KEDELAI EDAMAME PADA BERBAGAI DOSIS DAN WAKTU APLIKASI PUPUK HAYATI PADA TANAH GAMBUT - Dwi Zulfita (Fakultas Pertanian Universitas Janabadra, 2025)
Edamame grows well in tropical and subtropical climates with fairly high temperatures and relatively high rainfall, making it suitable for cultivation in Indonesia. This study aims to evaluate the interaction between the dose and timing of biological fertilizer application on the morphophysiological characteristics and yield of edamame soybeans grown on peat soil. Improving peatland productivity involves the application of biological fertilizers. The timing of biological fertilizer application influences nutrient absorption efficiency in plants. Plant growth analysis is a method used to assess the dynamics of photosynthesis by measuring the resulting Photosynthates. This study employed a factorial randomized block design (RAK) with three replications and two factors: the dose of biological fertilizer (d1 = 50 kg/ha, d2 = 75 kg/ha, d3 = 100 kg/ha) and the timing of biological fertilizer application (w1 = 2 and 4 MST; w2 = 2, 4, and 6 MST). The results demonstrated that the interaction of a 75 kg/ha biological fertilizer dose with the application timing of 2 and 4 MST provided the best plant growth analysis and yield components for edamame soybeans on peat soil.